The impact of liquidity on bank profitability - Etienne Bordeleau; Christopher Graham (Bank of Canada, 2010)
The recent crisis has underlined the importance of sound bank liquidity management. In response, regulators are devising new liquidity standards with the aim of making the financial system more stable and resilient. In this paper, the authors analyse the impact of liquid asset holdings on bank profitability for a sample of large U.S. and Canadian banks. Results suggest that profitability is improved for banks that hold some liquid assets, however, there is a point at which holding further liquid assets diminishes a banks' profitability, all else equal. Moreover, empirical evidence also suggests that this relationship varies depending on a bank's business model and the state of the economy. These results are particularly relevant as policymakers devise new standards establishing an appropriate level of liquidity for banks. While it is generally agreed upon that banks undervalued liquidity prior to the recent financial crisis, one must also consider the tradeoff between resilience to liquidity shocks and the cost of holding lower-yielding liquid assets as the latter may impact banks' ability to generate revenues, increase capital and extend credit.
Keywords: G21; G32; G33; 330; Financial system regulation and policies; Financial institutions; Financial stability; Finanzmarktkrise; Bankenkrise; Bankenreform; Bankenaufsicht; Bankenliquidität; USA; Kanada